2014
DOI: 10.3349/ymj.2014.55.5.1289
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Thiopurine Metabolites in Korean Pediatric Patients with Inflammatory Bowel Disease

Abstract: PurposeThis study aimed to assess the role of thiopurine S-methyltransferase (TPMT) and 6-thioguanine nucleotide (6-TGN) as predictors of clinical response and side effects to azathioprine (AZA), and estimate the optimal AZA dose in Korean pediatric inflammatory bowel disease (IBD) patients.Materials and MethodsOne hundred and nine pediatric IBD patients in whom AZA treatment was required were enrolled. Thiopurine metabolites were monitored since September 2010. Among them, 83 patients who had prescribed AZA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
3
12
0
Order By: Relevance
“…This is similar to rates seen in other parts of the world [12][13][14][15][16]. There were no homozygous variant genotypes found in this cohort of patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is similar to rates seen in other parts of the world [12][13][14][15][16]. There were no homozygous variant genotypes found in this cohort of patients.…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of two inactive alleles Thiopurine Methyltransferase Genotype Testing in Paediatric Patients in South Australia: A Retrospective Audit into Prescribing Practices is 1% in the sub-Saharan African population, 0.3% for Caucasians and perhaps even lower for the Asians [12][13][14]. In a study of Korean paediatric patients with IBD, 5.5% were heterozygotes and 0.9% was homozygous [15]. In contrast, 7.8% of paediatric patients with IBD examined in a study from Slovakia were heterozygotes [16] In Chilean children with ALL the frequency of heterozygotes was 8% [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with high level tolerated this metabolite level. It is previously reported that Asians have higher likelihood of thiopurine toxicity 21, 34. We had lowest toxicity as compared with that reported in the literature and did not observe any hepatotoxicity.…”
Section: Discussionsupporting
confidence: 51%
“…At this dose, median 6‐TGN level was 213 pmol/8 × 10 8 RBCs in active disease and 173 pmol/8 × 10 8 RBCs in patients with remission 29. A still lower dose, that is 1.2 mg/kg body weight, was used by Koreans, wherein the mean 6‐TGN level was 328 pmol/8 × 10 8 RBCs 34. In our study, patients on low dose of AZA (mean dose: 1.13 mg /kg, n = 57) had mean 6‐TGN level of 288 ± 240 pmol/8 × 10 8 RBCs and median 6‐TGN level of 217 (224) pmol/8 × 10 8 RBCs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation